Pelatihan Pembuatan Virgin Coconut Oil Bagi Kelompok Petani Nagari Surantih, Kecamatan Sutera, Kabupaten Pesisir Selatan - Ikhsandy, Ferry; Miftahurrahmah, Miftahurrahmah; Luthfi, Muhammad Zulfikar; Yahya, Agung Kurnia; Hibrah, Hibrah; N. H. , Harmiwati; Supriadi, Eko; Oktria, Dandi; Surya, Dhanu Fransgio Pratama (Politeknik ATI Padang, 2022)
West Sumatra has a high potential of coconut resources with most of it being processed for copra products. The pandemic situation in recent years has caused the price of copra products to fluctuate, so an alternative coconut processing is needed. Virgin Coconut Oil (VCO) is an alternative coconut product that can increase economic value of coconut and is needed as a supplement that can strengthen the body's immune system during the Covid-19 pandemic. One of the efforts to train the community to be able to process coconut into VCO is to conduct training activities that are directly located in the coconut farmer cluster, which is carried out in Sungai Sirah Village, South Coast District, West Sumatra. This community service activity aims to increase the competence of farmers in the village so that they can process the coconut produced into VCO, hence help their economy when the price of copra drops. The stages of the activity start from socialization, presentation on production process, and continued with demonstrating how to make VCO. Participants were divided into several small groups where they could immediately practice how to make this VCO with the correct fermentation steps. After the manufacturing process is well understood, the next step was training of how to do packaging and marketing. Farmers were trained on how to package products in order to get good quality product and then trained to sell VCO through online shop such as Facebook, Instagram, Tokopedia, etc. This activity helps add more insight in terms of processing and marketing, in which participants increase their knowledge and competence to form the basis for entrepreneurship of coconut processed products.